2016
DOI: 10.1017/apr.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Extremes for the inradius in the Poisson line tessellation

Abstract: A Poisson line tessellation is observed in the window Wρ := B(0, π −1/2 ρ 1/2 ), for ρ > 0. With each cell of the tessellation, we associate the inradius, which is the radius of the largest ball contained in the cell. Using Poisson approximation, we compute the limit distributions of the largest and smallest order statistics for the inradii of all cells whose nuclei are contained in Wρ as ρ goes to infinity. We additionally prove that the limit shape of the cells minimising the inradius is a triangle.The Poiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…We now compare our method to the one used in [4]. As mentioned on p. 3, our result is similar to Theorem 1.1 (ii) of [4].…”
Section: 31supporting
confidence: 60%
See 3 more Smart Citations
“…We now compare our method to the one used in [4]. As mentioned on p. 3, our result is similar to Theorem 1.1 (ii) of [4].…”
Section: 31supporting
confidence: 60%
“…We now compare our method to the one used in [4]. As mentioned on p. 3, our result is similar to Theorem 1.1 (ii) of [4]. However, the proof of this theorem is based on the method of moments, which leads to very technical computations of combinatorics, and does not provide rate of convergence for the Poisson approximation.…”
Section: 31supporting
confidence: 53%
See 2 more Smart Citations
“…This result is the answer to the Kendall problem (formulated for the zero cell of a Poisson hyperplane mosaic) and is adapted to the typical cell of the mosaic in [7]. In [4] cells with large (and small) inradius and with center in a window are considered. For dimension d = 2 it is shown that the limit distribution of the largest and smallest order statistics for the inradii converges to a Poisson distribution when the size of the window goes to infinity.…”
Section: Introductionmentioning
confidence: 99%